MathOverflow is a question and answer site for professional mathematicians. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Trying to understand a result in a representation theoretical paper, I realized that it implies the following elementary identity for symmetric functions. My question is whether this identity is true, known, and whether it has a direct proof. It might also happen that this identity is simpler than I think.

Let $d$ be a natural number. For $0\leq k\leq d$ let $e_k(z_1\dots,z_d)$ denote the $k$th elementary symmetric polynomial in $d$ variables, namely $$e_k(z_1\dots,z_d)=\sum_{1\leq i_1<\dots <i_k\leq d}z_{i_1}\dots z_{i_k}.$$

Let $x$ be a variable. The relevant identity is \begin{eqnarray*} \sum_{k=0}^d (-1)^k(x-d)^{2k}\cdot e_{d-k}((x-d+1)^2,\dots,(x-1)^2,x^2)=\\ d!\cdot (2x-2d+1)\dots (2x-d-1) (2x-d).\end{eqnarray*}

Notice that the right hand side is a polynomial in $x$ of degree $d$, while the left hand side has a priori degree at most $2d$ only.

share|cite|improve this question
up vote 12 down vote accepted

Viete formula gives $\sum_{k=0}^{d} t^k e_{d-k}\left(\alpha_0,\ldots,\alpha_{d-1}\right)=(t+\alpha_1)\ldots(t+\alpha_d).$

Therefore (substituing $t=-(x-d)^2$ and $\alpha_j=(x-j)^2$), LHS is equal to $\prod_{j=0}^{d-1} \left(-(x-d)^2+(x-j)^2\right)= \prod_{j=0}^{d-1} (2x-j-d)(d-j)=d!\prod_{k=d}^{2d-1} (2x-k)$

which is exactly the RHS.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.